Thyroid hormones, mitochondria, aging, and cancer - Glinsky, Gennadi; Hercbergs, Aleck; Davis, Paul J. (Frontiers in Endocrinology, 2026)
In mammals, thyroid hormones (THs) and their metabolites exert their regulatory effects on metabolism, oxygen consumption, energy generation and expenditure, and gene expression via genomic and non-genomic mechanisms by binding to different types of THs receptors. THs binding to nuclear receptors engages the genomic pathway, while binding to receptors on mitochondria or cell membrane receptors located on thyrointegrins initiates nongenomic mode of actions. In this contribution, we review the effects of THs and their metabolites on mitochondrial structure and functions, including both classical and non-canonical features, in various pathophysiological conditions, focusing on aging, stemness, and cancer. Our analysis indicates that nongenomic mode of actions of THs on mitochondria appear affected during aging and its alterations may contributed to development of cancer and other aging-associated disorders.